KYPHOPLASTY AND VERTEBROPLASTY IN THE TREATMENT OF OSTEOPOROTIC VERTEBRAL FRACTURES - García Ortiz Uriel Nahum; Fuentes Rivera Miguel Ángel; González Moga Amado; Santos Benitez Hugo Alberto (Coluna/Columna)
ABSTRACT Objective: To compare these procedures in the treatment of osteoporotic vertebral compression fractures. Methods: Patients who underwent vertebral augmentation procedures between March 2010 and October 2016 were selected for the study. Kyphosis, anterior vertebral height, Oswestry Disability Index (ODI), Visual Analog Scale (VAS), number of portals, cement volume, and complications were recorded. The results were analyzed by difference of the means. Results: Sixty-eight patients were selected, accounting for 105 procedures. A statistically significant improvement was observed in VAS and ODI with both procedures (p<0.001) without statistically significant difference between them, regardless of the number of portals or cement applied. There was a high correlation between kyphosis correction and ODI improvement (p =0.012). Conclusions: Both vertebroplasty and kyphoplasty are effective procedures for the treatment of vertebral compression fractures. We found no significant difference between both procedures. The high correlation between improvement of kyphosis and ODI suggests that these procedures are better than conservative treatment to improve the quality of life of patients, however more studies are required to reach a final conclusion. Level of Evidence III; Retrospective comparative study.